Expanding patient access to psychiatry and mental health supports: early impacts of the Nova Scotia health rapid access and stabilization program - Adu, Medard K.; Obeng Nkrumah, Samuel; Agyapong, Belinda; Ezeanozie, Ngozi; Eboreime, Ejemai; Obuobi-Donkor, Gloria; Sridharan, Sanjana; Morrison, Jason; Taylor, Bryanne; MacKinnon, Monica; Awara, Mahmoud; Wang, JianLi; et al. (Frontiers in Psychiatry, 2026)
BackgroundThe average Canadian waits several weeks to months to access a psychiatric consultation and other forms of mental health support even after referral by a primary healthcare provider (PHP). This delay can worsen conditions, leading to costly interventions like emergency department visits, unplanned hospital admissions, and extended inpatient care. To address these challenges, Nova Scotia Health launched the Rapid Access and Stabilization Program (RASP) in April 2023 at the QEII Health Sciences Centre in Halifax to enhance mental health care capacity and accessibility.ObjectivesThis study aims to evaluate the early impact of rapid access to psychiatry consultations compared to standard care and assess the service user experience of the RASP.MethodsThis is an exploratory, descriptive study that utilizes retrospective secondary data to examine patient access to psychiatric consultations within the Mental Health and Addictions Program (MHAP) before RASP implementation (fiscal years 2021/2022 and 2022/2023) with data from the first year of RASP operation (fiscal year 2023/2024). A cross-sectional, survey-based approach was employed to assess patient satisfaction with RASP. Data on psychiatric consultations were obtained from provincial administrative sources, while patient satisfaction data were collected via the RASP satisfaction survey administered after consultations. Quantitative data were analyzed using descriptive and inferential statistics, and qualitative data from open-ended survey responses were manually analyzed using a content analysis approach.ResultsIn its first year, RASP provided psychiatric consultations to 960 unique patients. During the 2023/2024 fiscal year, there was a 1226.7% increase in PHP-referred patients receiving psychiatric assessments compared to 2022/2023. Additionally, the number of new patients assessed by a psychiatrist, either through PHP referral or transfer of care from mental health clinicians, increased by 102% compared to the previous fiscal year. A total of 487 participants responded to the satisfaction survey, with a mean overall satisfaction score of 9.31 (SD ± 1.42) on a scale from 1 (not satisfied) to 10 (best experience). Of the respondents, 80.5% indicated they would return for an assessment if needed, and 97.3% said they would recommend the program to others.ConclusionThis study reveals a substantial increase in access to psychiatric care through RASP and the program’s effectiveness is underscored by high overall satisfaction. These findings emphasize the program’s success in delivering quality mental health care while also identifying opportunities for further improvement to ensure continued patient satisfaction and service excellence.